The effect of selenium fertilizers on the selenium content of barley, spring wheat and potatoes - Korkman, Johan (Agricultural and Food Science, 1980)
When Se-enriched fertilizers were given to barley and spring wheat on fine sand soils in Southern Finland the Se content in the grain was raised as follows: 50 g Se/ha increased the Se content by around 50 µg/kg; 250 g Se/ha by appr. 400 µg/kg; and 500 g Se/ha by a little more than 900 µg/kg. The selenium content of potatoes rose to 100 µg Se/kg dry matter when the soil was enriched with 500 g Se in the form of Na2SeO2 per hectare. The selenium content of potatoes was found to be very low when no added selenium was given. The selenium content of potatoes did not fall when the potatoes were boiled.